12‐hr shifts in nursing: Do they remove unproductive time and information loss or do they reduce education and discussion opportunities for nurses? A cross‐sectional study in 12 European countries. Issue 1 (28th October 2019) - Dall'Ora, Chiara; Griffiths, Peter; Emmanuel, Talia; Rafferty, Anne Marie; Ewings, Sean; ,
Abstract: Aims and objectives: To examine the association between registered nurses' (referred to as "nurses" for brevity) shifts of 12 hr or more and presence of continuing educational programmes; ability to discuss patient care with other nurses; assignments that foster continuity of care; and patient care information being lost during handovers. Background: The introduction of long shifts (i.e., shifts of 12 hr or more) remains controversial. While there are claims of efficiency, studies have shown long shifts to be associated with adverse effects on quality of care. Efficiency claims are predicated on the assumption that long shifts reduce overlaps between shifts; these overlaps are believed to be unproductive and dangerous. However, there are potentially valuable educational and communication activities that occur during these overlaps. Design: Cross‐sectional survey of 31, 627 nurses within 487 hospitals in 12 European countries. Methods: The associations were measured through generalised linear mixed models. The study methods were compliant with the STROBE checklist. Results: When nurses worked shifts of 12 hr or more, they were less likely to report having continuing educational programmes; and time to discuss patient care with other nurses, compared to nurses working 8 hr or less. Nurses working shifts of 12 hr or more were less likely to report assignments that foster continuity of care, albeit the association was not significant. Similarly, working long shifts was associated with reports of patient care information being lost during handovers, although association was not significant. Conclusion: Working shifts of 12 hr or more is associated with reduced educational activities and fewer opportunities to discuss patient care, with potential negative consequences for safe and effective care. Relevance to clinical practice: Implementation of long shifts should be questioned, as reduced opportunity to discuss care or participate in educational activities may jeopardise the quality and safety of care for patients.